Implementation of Islamic Education Methods from a Fiqh Perspective to Improve Learning Quality - Fajar Aswati; Chanifudin Chanifudin (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This article aims to examine the role of Islamic education based on fiqh in enhancing the quality of learning and shaping individuals who are intellectually, morally, and spiritually competent, as well as capable of facing the challenges of globalization while adhering to Islamic values. The research method employed in this study is descriptive qualitative. Education is a lifelong process that develops individuals to live meaningfully and sustain life. The role of fiqh in education, particularly at the madrasa level, is crucial in equipping students with knowledge and understanding of Islamic teachings, especially regarding worship and morality. Through comprehensive and holistic learning, Islamic education seeks to cultivate well-rounded individuals (insan kamil) who are not only successful in worldly matters but also attain eternal happiness in the hereafter, while preparing the younger generation to confront the challenges of modern times without losing their identity or Islamic values.